24.3k views
1 vote
Sum difference and product of two functions

Sum difference and product of two functions-example-1

1 Answer

7 votes

Answer:

1)
(g+h)(x)=4x^2+x+2

2)
(g-h)(x)=-4x^2+x+2

3)
(g\bullet h)(-3)=-36

Explanation:

The given functions are


g(x)=x+2

and


h(x)=4x^2

1)
(g+h)(x)=g(x)+h(x)

This implies that;


(g+h)(x)=x+2+4x^2

Rewrite in standard form to obtain
(g+h)(x)=4x^2+x+2

2)
(g-h)(x)=g(x)-h(x)

This implies that;


(g-h)(x)=x+2-4x^2

Rewrite in standard form to obtain
(g+h)(x)=-4x^2+x+2

3)
(g\bullet h)(x)=(x+2)(4x^2)

We now substitute
x=-3 to obtain;


(g\bullet h)(-3)=(-3+2)(4(-3)^2)


(g\bullet h)(-3)=(-1)(36)


(g\bullet h)(-3)=-36

User Dhein
by
5.8k points